Development of animal models for schizophrenia - Arguello, P. Alexander (The Company of Biologists Limited, 2010)
Schizophrenia is a devastating psychiatric disorder that affects around 1% of the population worldwide. The disease is characterized by ‘positive symptoms’, ‘negative symptoms’ and cognitive deficits. Over the last 60 years, a large number of family, twin and adoption studies have clearly demonstrated a strong genetic component for schizophrenia, but the mode of inheritance of the disease is complex and, in all likelihood, involves contribution from multiple genes in conjunction with environmental and stochastic factors. Recently, several genome-wide scans have demonstrated that rare alleles contribute significantly to schizophrenia risk. Assessments of rare variants have identified specific and probably causative, disease-associated structural mutations or copy number variants (CNVs, which result from genomic gains or losses). The fact that the effects of such lesions are transparent allows the generation of etiologically valid animal models and the opportunity to explore the molecular, cellular and circuit-level abnormalities underlying the expression of psychopathology. To date, the most common genomic structural rearrangements that are unequivocally associated with the development of schizophrenia, are de novo microdeletions of the 22q11.2 locus. Fortunately, the human 22q11.2 locus is conserved within the syntenic region of mouse chromosome 16, which harbors nearly all orthologues of the human genes. This has made it possible to engineer genetically faithful, and thus etiologically valid, animal models of this schizophrenia susceptibility locus.